Sequence variation within the rRNA gene loci of 12 Drosophila species - Stage, Deborah E.; Eickbush, Thomas H. (Genome Research, 2007)
Concerted evolution maintains at near identity the hundreds of tandemly arrayed ribosomal RNA (rRNA) genes and their spacers present in any eukaryote. Few comprehensive attempts have been made to directly measure the identity between the rDNA units. We used the original sequencing reads (trace archives) available through the whole-genome shotgun sequencing projects of 12 Drosophila species to locate the sequence variants within the 7.8–8.2 kb transcribed portions of the rDNA units. Three to 18 variants were identified in >3% of the total rDNA units from 11 species. Species where the rDNA units are present on multiple chromosomes exhibited only minor increases in sequence variation. Variants were 10–20 times more abundant in the noncoding compared with the coding regions of the rDNA unit. Within the coding regions, variants were three to eight times more abundant in the expansion compared with the conserved core regions. The distribution of variants was largely consistent with models of concerted evolution in which there is uniform recombination across the transcribed portion of the unit with the frequency of standing variants dependent upon the selection pressure to preserve that sequence. However, the 28S gene was found to contain fewer variants than the 18S gene despite evolving 2.5-fold faster. We postulate that the fewer variants in the 28S gene is due to localized gene conversion or DNA repair triggered by the activity of retrotransposable elements that are specialized for insertion into the 28S genes of these species.